Spontaneous lung colonization in the cystic fibrosis rat model is linked to gastrointestinal obstruction - Mikayla Murphree-Terry; Johnathan D. Keith; Ashley M. Oden; Susan E. Birket (mBio)
ABSTRACT Cystic fibrosis (CF) is a genetic disease caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene, resulting in CFTR protein dysfunction. CFTR dysfunction has multi-organ consequences, leading to dehydrated mucus that is adherent to epithelia. In the lungs, this leads to recalcitrant infections with bacteria such as Pseudomonas aeruginosa. In the gut, mucus-laden feces can adhere to the intestines, resulting in distal intestinal obstruction syndrome (DIOS). There is limited information on how lung colonization and DIOS are correlated in people with CF (pwCF). In this novel work, we describe the development of spontaneous lung colonization of CF pathogens in young (<3 months old) CF rats, preceding the development of DIOS. Once DIOS is established, the lung microbiome becomes predominated by taxa also observed in the feces. Induced infection with P. aeruginosa in the CF rats reflects data found in pwCF, as once CF rats are infected, they retain a higher relative abundance of P. aeruginosa than their healthy agemates. Finally, we found that ivacaftor treatment favors a healthier gut microbiome in CF rats, decreasing the relative abundance of Escherichia coli. These results indicate that the CF rat model is recapitulative of human CF disease with the spontaneous lung colonization of traditional CF pathogens and maintenance of P. aeruginosa after induced infection. Furthermore, these results indicate a possible role for the gut-lung axis in lung colonization and DIOS in CF.IMPORTANCEThese data describe for the first time the development of spontaneous lung colonization in the cystic fibrosis (CF) rat model, a hallmark aspect of human CF disease. We also find that CF rats infected with Pseudomonas aeruginosa maintain higher relative abundance following chronic infection as compared to healthy rats, similar to those is seen in people with CF. Additionally, we describe the possible contribution of the gut-lung axis linking lung health with distal intestinal obstruction syndrome, a relationship largely unexplored in the context of CF.